Intraorbital corticosteroid injection for the treatment of IgG4-related ophthalmic disease. Issue 5 (21st August 2015) - Andrew, Nicholas H; Gajdatsy, Adam; Selva, Dinesh
Abstract : Aim: To review the efficacy of intraorbital corticosteroid injection for the treatment of IgG4-related ophthalmic disease (IgG4-ROD). Methods: This study was a retrospective twin-centre histopathology review and observational case series. A chart review was undertaken for 10 cases of biopsy-confirmed IgG4-ROD treated with intraorbital corticosteroid injection. The main outcome measures were the magnitude, onset and duration of the clinical response. Results: All cases received intraorbital injection(s) of 20 or 40 mg doses of triamcinolone acetonide suspension (Kenacort-A 40, Bristol-Myers Squibb, Australia). Intraorbital corticosteroid injection was associated with a swift positive response in all cases. 50% of cases achieved complete and sustained clinical remission during mean follow-up of 41 months. This was achieved with a single injection in three cases and with repeat injections in two cases. Peak clinical improvement was reached in ≤7 days following 61% of injections. 60% of cases suffered relapse and 56% of relapses occurred during weeks 3 or 4 following injection. Sclerosing histology was associated with a clinical response that was gradual in onset (p=0.01) and that tended to be incomplete (p=0.4). There were no complications of injection other than brief discomfort. Conclusions: Intraorbital injection of corticosteroid may be a useful treatment option for IgG4-ROD. It may have a role as a first-line therapy in selected cases of IgG4-ROD centred in the anterior orbit. However, most cases require repeat injections due to incomplete response and relapse.